Analisis Metode Pembelajaran Bahasa Arab di Madrasah Aliyah Laboratorium UINSU Medan - Nahda Sahriani; Zulfahmi Lubis (MANAZHIM, 2023)
This research aims to determine the method of learning Arabic in the Madrasah Aliyah Labolatorium UINSU Medan by using a type of field research with qualitative research method, which is the object of research for Arabic subject teachers and the methods used in learning Arabic. The method used at the Madrasah Aliyah Labolatorium UINSU is tu use various method and adapt tu the material to be tought and also the methods that are commonly used, namerly the group discussion method, demonstration method, field trip method and translation method. The method used was implemented well an made it easier for students at the Madrasah Aliyah Labolatorium UINSU to understand the lessons conveyed by the teacher. The importence of using methods and choosing metgots that are appropriate to the material ti be taught in learning Arabic will make it easier for students to understand learning and create affective an efficient learning.